Social interaction and stock market participation: Evidence from British panel data - Sarah Brown; Karl Taylor (Institute for the Study of Labor (IZA), 2010)
This paper uses data from the British National Child Development Study to investigate the relationship between social interaction and participation in the stock market through holding stocks and/or shares at the individual level. In accordance with the existing literature, the results reveal that a positive relationship exists between social interaction and stock market participation, when both are measured concurrently. Furthermore, this relationship prevails across a range of measures of social interaction and social capital. In addition, we make a potentially important contribution to the existing literature by exploiting the panel nature of the data in order to explore the robustness of the cross-sectional findings. We find that the positive relationship between stock market participation and social interaction prevails within a fixed effects logit framework, which controls for time invariant unobserved effects.
Keywords: D12; D14; D71; 330; Social capital; social interaction; stock market participation; Soziale Beziehungen; Anlageverhalten; Aktionäre; Social Capital; Großbritannien